The greater German Reich and the Jews : Nazi persecution policies in the annexed territories 1935-1945 - Gruner, Wolf, 1960-; Osterloh, Jörg, 1967-; Heise, Bernard (War and genocide, 2015)
Between 1935 and 1940, the Nazis incorporated large portions of Europe into the German Reich. The contributors to this volume analyze the evolving anti-Jewish policies in the annexed territories and their impact on the Jewish population, as well as the attitudes and actions of non-Jews, Germans, and indigenous populations. They demonstrate that diverse anti-Jewish policies developed in the different territories, which in turn affected practices in other regions and even influenced Berlin's decisions. Having these systematic studies together in one volume enables a comparison - based on the most recent research - between anti-Jewish policies in the areas annexed by the Nazi state. The results of this prizewinning book call into question the common assumption that one central plan for persecution extended across Nazi-occupied Europe, shifting the focus onto differing regional German initiatives and illuminating the cooperation of Indigenous institutions.